Effect of plant spacing and nutrient management on bulb yield of ratoon onion (Bangladesh Journal of Agricultural Research, 2026)
A field experiment was conducted at Regional Spices Research Centre, BARI, Gazipur during two growing seasons of 2020-2021 and 2021-2022. The objective of the study was to find out the suitable plant spacing and develop a nutrient management package for maximizing the yield of ratoon onion. The experiment was conducted in a Factorial Randomized Complete Block Design having three replications. There were 9 treatments comprising three levels of plant spacing: 10 cm X 10 cm, 15 cm X 10 cm and 20 cm X 10 cm with three nutrient management packages: Soil test basis (N90P37K80S15Zn1.5B1 kg ha-1) with cowdung 3 t ha-1, RDF (N110P45K120S30Zn3B1.5 kg ha-1) with cowdung 5 t ha-1 and farmer’s practices (N120P50K85S20kg ha-1). Results revealed significant effect for plant spacing and nutrient management as well as their interaction on the yield components and bulb yield of ratoon onion. The highest bulb yield (12.1 and 14.33 t ha-1 in 2020-2021 and 2021-2022, respectively), was obtained with plant spacing (10 cm x 10 cm) along with the RDF (N110P45K120S30Zn3B1.5 kg ha-1) with cowdung 5 t ha-1. The cost benefit analyses also showed the maximum net income (594857 taka) from the same treatment combination. Therefore, the same treatment package (10 cm x 10 cm spacing and N110P45K120S30Zn3B1.5 kg ha-1 with cowdung 5 t ha-1) may be recommended for maximizing the bulb yield of ratoon onion in Grey Terrace Soil of Madhupur Tract (AEZ-28) at Gazipur and under similar agro-climatic condition elsewhere in the country.Bangladesh J. Agril. Res. 47(4): 451-461, December 2022